KONSTRUKSI METODOLOGI PENDIDIKAN ISLAM: Analisis Kritis Hadis Tarbawi, Syarah Ulama, Dan Relevansinya Terhadap Teori Pembelajaran Modern - ibn bar, azis; Abdul Mufid (Sekolah Tinggi Agama Islam (STAI) Khozinatul Ulum Blora, 2026)
Education is a fundamental pillar of human civilization, and Islam positions it as the primary means of shaping quality individuals as khalifah fil ardh. Hadith Tarbawi, as the second source of Islamic law after the Qur'an, contains pedagogical principles that were directly implemented by the Prophet Muhammad SAW. This article aims to examine and analyze tarbawi hadiths in order to formulate an Islamic educational methodology relevant to contemporary contexts. This study employs a library research method with a descriptive-analytical approach. Data were collected from primary hadith sources, particularly Ṣaḥīḥ al-Bukhārī and Ṣaḥīḥ Muslim, as well as classical and modern tarbawi literature, and were analyzed using the framework of modern Islamic pedagogy. The findings reveal that: (1) the Prophet’s educational methodology is holistic, encompassing cognitive, affective, and psychomotor domains; and (2) the methods applied include al-Qaṣaṣ al-Ḥaqīqī (authentic storytelling), al-Ḥiwār (dialogue), al-Targhīb wa al-Tarhīb (motivation and warning), al-Maw‘iẓah al-Ḥasanah (constructive advice), and al-Uswah al-Ḥasanah (exemplary modeling). The study concludes that integrating tarbawi methodology into modern educational systems is a crucial solution to addressing the current moral crisis and character degradation.